CTIM-16. INTERSTITIAL PHOTODYNAMIC THERAPY WITH 5-ALA FOR MALIGNANT GLIOMA RECURRENCES. (9th November 2020) - Lietke, Stefanie; Schmutzer, Michael; Schwartz, Christoph; Weller, Jonathan; Aumiller, Maximilian; Heckl, Christian; Forbrig, Robert; Niyazi, Maximilian; Stepp, Herbert; Sroka, Ronald; Tonn, Joerg-Christian; Rühm, Adrian; et al.
Abstract: Interstitial photodynamic therapy (iPDT) using 5-aminolevulinic acid (5-ALA) induced protoporphyrin IX (PPIX) as a cytotoxic photosensitizer has been shown to be a feasible treatment option for malignant gliomas. We present outcome measures and a risk profile analysis of salvage iPDT in a large monocentric cohort with local tumor recurrence following standard therapy. This study included consecutive adult patients undergoing salvage iPDT for small, circumscribed, biopsy-proven malignant glioma recurrences not deemed eligible for safe complete resection of contrast enhancing tumor. A modified 3-D treatment-planning software was used to calculate the treatment-volume and the position of the stereotactic light diffusers within the lesion. Outcome measurements included estimated time-to-treatment-failure (TTF), post-recurrence survival (PRS) and the risk profile of iPDT. Prognostic factors were obtained from logistic regression models. The institutional review board approved the study. A total of 44 patients (median age: 49.4 years, range 33.4–87.0 years, 17 female) were included. Recurrent tumors included 37/44 glioblastomas WHO grade IV and 7/44 anaplastic astrocytomas WHO grade III. Thirty (68.2%) tumors were MGMT methylated. Median treatment volume was 3.3 ccm (range, 0.5–22.8 ccm). A median number of 4 (range: 3–8) laser fibers were used. Median illumination time was 60min (range: 60–167 min). Symptomatic edema (8/44) or intratumoral hemorrhagic imbibition (7/44) did not result in any permanent morbidity. Median TTF was 7.1 months and median PRS was 13.0 months. The 2- and 5-years PRS rates were 25.0% and 4.5%. Treatment response was heterogeneous and not significantly associated with patient characteristics, treatment-related factors or molecular markers. In conclusion, iPDT was associated with promising outcome measurements in local malignant glioma recurrences in highly selected patients. Transient neurologic deterioration did not lead to any permanent morbidity. The procedure deserves further prospective evaluation particularly to identify mechanisms of favorable treatment response and prognostic factors associated with long-term survival.